Refusal Speech Act Used By Male And Female Sellers At Pasar Sambu Medan - Lili Sowari Siregar; Lastri Wahyuni Manurung; Harpen H.P. Silitonga; Tutiarny Naibaho (Universitas Pahlawan Tuanku Tambusai, 2023)
This study deal with the analysis of refusal speech act used by male and female sellers at Pasar Sambu Medan. This study attempted two answers to the problems, namely (1) What are the dominant refusal speech acts used by male and female sellers at Pasar Sambu Medan, and (2) What are the difference of refusal speech act used by male and female sellersat Pasar Sambu Medan. This study used descriptive qualitative research. The data of this study was refusals in bargaining between sellers and buyers that took at Pasar Sambu Medan. The collecting data has applied observation and audio recording as the instrument. The finding of this study showed that male sellers used performative statement strategy most dominant which implicitlyindicated that they tended to refuse the buyer’s offered in a direct way. Instead female sellers, used avoidance/hedging most dominant which indicated that they preferred to refused their buyer’s offered in an indirect way. This study found the difference refusal speech act used by male and female sellers was male sellers refused more than female sellers.